2016
DOI: 10.1101/gad.287524.116
|View full text |Cite
|
Sign up to set email alerts
|

Recent insights into the function of autophagy in cancer

Abstract: Macroautophagy (referred to here as autophagy) is induced by starvation to capture and degrade intracellular proteins and organelles in lysosomes, which recycles intracellular components to sustain metabolism and survival. Autophagy also plays a major homeostatic role in controlling protein and organelle quality and quantity. Dysfunctional autophagy contributes to many diseases. In cancer, autophagy can be neutral, tumor-suppressive, or tumorpromoting in different contexts. Large-scale genomic analysis of huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
627
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 689 publications
(639 citation statements)
references
References 161 publications
(202 reference statements)
7
627
0
5
Order By: Relevance
“…However, under some conditions, it may play a suppressive role and lead to cancer cell death. Cell death is most commonly associated with apoptosis, but it can also occur via autophagic cell death (47,48). Many studies have demonstrated that these two types of cell death are predominantly distinctive but that cross-talk also occurs between them.…”
Section: Discussionmentioning
confidence: 99%
“…However, under some conditions, it may play a suppressive role and lead to cancer cell death. Cell death is most commonly associated with apoptosis, but it can also occur via autophagic cell death (47,48). Many studies have demonstrated that these two types of cell death are predominantly distinctive but that cross-talk also occurs between them.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular Physiology and Biochemistry [30][31][32], especially in cancer metastasis [33]. Therefore, our results are important for the understanding of autophagy abnormalities and RCC development and metastasis.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…Since mitophagy is reliant on the general autophagy machinery for formation of the pre-initiation and initiation complexes, defects in mitophagy are epistatic to defects in general autophagy. However, perhaps because general autophagy plays so many critical roles in the emergence of tumor cells, core autophagy genes have rarely been found mutated in human cancers [14]. Indeed, debate remains over whether Beclin-1, a core component of the autophagy initiation complex, that is mono-allelically deleted in breast, ovarian and other cancers [15,16], is a bona fide tumor suppressor gene or a merely a passenger lesion whose deletion is driven by selection for loss of the adjacent BRCA1 gene [17].…”
Section: Mechanics Of Mitophagy and Key Mitophagy Proteinsmentioning
confidence: 99%